Assessment of the FSM value-chain in Sri Lanka - Ulrich, Andreas; Taron, Avinandan; Jayathilake, Nilanthi (CGIAR Research Program on Water, Land and Ecosystems, 2019)
Over 85% of Sri Lanka’s population uses on-site sanitation systems, yet regular desludging is rare and treatment coverage remains low. Only a few cities, like Colombo, have designated disposal sites; in many areas, fecal sludge is either dumped untreated or sent to malfunctioning or abandoned treatment plants. While some municipalities operate Decentralized Wastewater Treatment Systems (DEWATS) and Faecal Sludge Treatment Plants (FSTPs), many lack technical capacity, maintenance funding, and access to reuse markets.Local Authorities manage desludging but often lack proper equipment and trained staff. Private operators are active, especially in urban areas, but face limited access to formal disposal points. Cost recovery is low, and most services are not financially sustainable. Although some plants co-compost sludge with organic waste, such reuse is inconsistent and unregulated.Institutional roles are fragmented across multiple agencies with no unified oversight or standard guidelines. To scale safe and sustainable FSM, the report highlights the need for standardized designs, operational training, public-private collaboration, and the development of circular business models linking sanitation with resource recovery.